2010
DOI: 10.1590/s1516-89132010000200018
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis of the parental contribution of Piaractus mesopotamicus to the production of offspring in the semi-natural system of reproduction

Abstract: The objective of this study was to evaluate the genetic diversity and the parental contribution of Piaractus mesopotamicus in the production of offspring in the semi-natural system of reproduction. Twenty parental fishes (eleven males and nine females) and the total of 100 larvae were evaluated by microsatellite marker. The parents and offspring had thirty-one alleles and heterozygosity of 0.550 and 0.563, respectively. The females were fertilised by two up to six males while the males fertilised three up to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
3
9
0
1
Order By: Relevance
“…This disequilibrium may be due to the number of samples collected. These results are similar to those obtained by Povh et al (2010) where they observed different patterns of linkage disequilibrium in the parental and progeny fishes, without affecting the estimates of genetic diversity.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This disequilibrium may be due to the number of samples collected. These results are similar to those obtained by Povh et al (2010) where they observed different patterns of linkage disequilibrium in the parental and progeny fishes, without affecting the estimates of genetic diversity.…”
Section: Resultssupporting
confidence: 90%
“…The breeding system used in mating (Lopera Povh et al, 2010) and the use of sequential or simultaneous semen during artificial fertilization (Withler and Beacham, 1994) are also factors that may affect the genetic variability of progeny used in stocking programs. Reproductive management is of fundamental importance to preserve the genetic diversity of juveniles which will participate in the stocking programs.…”
Section: Resultsmentioning
confidence: 99%
“…These results were expected because the broodstocks were formed from the identical ancestral, from the Paraná River (foundation effect), and identical individuals were introduced from the Tietê and Grande rivers. Additional factors, such as the raising system (i.e., a small group of broodstocks, sexual proportions, reproductive dominance, endogamy, high variations among individuals during reproduction) and fluctuation in population size over time, can also be influenced by the homogeneity of current broodstocks (CAMERON-BROWN et al, 2005;BORREL et al, 2007;FOPP-BAYAT et al, 2010;LOPERA-BARRERO et al, 2010b;POVH et al, 2010).…”
Section: Genetic Structurementioning
confidence: 99%
“…Although these programs have been performed over several decades, studies of genetic and environmental efficiencies are necessary (AGOSTINHO et al, 2005;POVH et al, 2010). However, many programs have been unsuccessful because of the inappropriate management of broodstocks (BSs) (BORREL et al, 2007;LOPERA-BARRERO, 2009) and the non-monitoring of WPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation